Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Discovery of cytotoxic 1,4-benzodioxane oxyneolignan analogues from Glechoma longituba - Ming-Ming Yuan; Xi Wu; Yang-Bing Zheng; Yu-Lin Feng; Er-Lei Xie (Phytochemistry, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

From organic wastes to feed, fertilizer, fuels and materials: A systems review of insect farming and biorefinery pathways in urban and agroecosystems - Phei Er Kee; Diana Jose; Dillirani Nagarajan; Malinee Sriariyanun; Yu-Shen Cheng (Agricultural Systems, 2026)

Correction: YAP regulates porcine skin-derived stem cells self-renewal partly by repressing Wnt/β-catenin signaling pathway - Hong-Chen Yan; Yu Sun; Ming-Yu Zhang; Shu-Er Zhang; Jia-Dong Sun; Paul W. Dyce; Francesca Gioia Klinger; Massimo De Felici; Wei Shen; Shun-Feng Cheng (Histochemistry and Cell Biology, 2026)

A Protective Role for Melatonin: Enhancing Heat Tolerance in Alisma plantago-aquatica Seedlings - Wen-hui Chen; Jiao Wang; Ke-yu Wang; De-qiang Li; Zi-zhong Tang; Yang-er Chen; Shu Yuan; Lu Zhang; Ming Yuan (Journal of Plant Growth Regulation, 2026)

Pulse electric field-assisted preparation of soy protein isolate-based films with excellent mechanical strength and UV barrier performance - Ying Li; Xiu-Er Luo; Yu-Huan Geng; Wen-Hong Gao; Shuai Zhang; Zhong Han (Innovative Food Science & Emerging Technologies, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

First macrofossil record of Selaginellites from the Jurassic of northwestern China - Zhi-Hui Song; Zhuo-Er Wang; Huai Wang; Xu Li; Jing-Yu Wu; Su-Ting Ding (Review of Palaeobotany and Palynology, 2026)

Physics-informed neural network for deep learning of finned-tube evaporator performance: From the perspective of system modeling - Shu-Yu Lu; Er-Qi Chen; Tian-Ya-Hui Xu; Xing-Yu Liang; Chun-Lu Zhang (International Journal of Refrigeration, 2026)

Design, fabrication and multiple failure behavior of carbon fiber composite circumferential corrugated reinforced cylindrical shells under hydrostatic pressure - Yang-Xu Chong; Jin-Shui Yang; Da-Long Ding; Fang Yang; Hai-Dong Li; Yu-Yin Wei; Er Zhang; Jia-Dong Zeng; Guo-Tao Chen (Ocean Engineering, 2026)

Umifenovir protects Procambarus clarkii against white spot syndrome virus by suppressing viral replication and modulating innate immunity - Cheng Chen; Bo-Han Li; Chao-Yu Wang; Er-Long Wang; Tian-Qiang Liu; Zhe Zhao (Fish & Shellfish Immunology, 2026)

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Research on rule of law system for marine environmental protection in the Guangdong-Hong Kong-Macao Greater Bay Area - Ke Zhang; Er-He Chen; Yu-Lin Chen; Jun-Jie Li; Tao Huang; Wei Liu; Si-Hao Wei; Yu-Kang Tu (Frontiers in Marine Science, 2026)
The development of a legal system for marine environmental protection in the Guangdong-Hong Kong-Macao Greater Bay Area is a critical issue for cross-border ecological governance under the unique context of "One Country, Two Systems, Three Jurisdictions." This issue directly affects regional ecological security and the high-quality development of the marine economy. This paper uses comparative law and empirical analysis to systematically review the institutional frameworks and current practices of the three regions across four dimensions: Legislation, law enforcement, judicial adjudication, and legal regulation of public participation. The study finds that the current system faces core difficulties, including a disconnect in legislative coordination mechanisms, insufficient effectiveness in joint law enforcement, uncoordinated judicial collaboration, and insufficient legal safeguards for public participation. The root causes lie in the differences between regional legal systems, the absence of coordination mechanisms, poor resource integration, and fragmented participation channels. Based on this, the paper proposes a comprehensive improvement path. At the legislative level, we should establish a normalized coordination mechanism to promote the alignment of rules and standards. At the enforcement level, we should build a unified coordination platform to deepen cross-border collaboration and resource sharing. At the judicial level, we should improve cross-border collaboration norms and improve mechanisms for identifying and repairing ecological damage. At the level of public participation, we should build a unified cross-border platform to strengthen collaborative systems and public interest cooperation. The research aims to provide a governance model for regional marine environmental protection under "One Country, Two Systems, Three Jurisdictions," offering theoretical support and practical guidance for solving cross-border ecological governance problems, and assisting in the construction of a strong maritime nation and the improvement of the global marine governance system.

Sustainable alternative to biological nitrogen removal: Is ammonia recovery from municipal wastewater a fantasy? - Wenjie Hao; Yuanyuan Yu; Yi Gong; Ge’er Wang; Maoqin Ao; Minyuan Han; Haoquan Zhang; Qingxiang Guo; Jingmei Yao; Yi Yang; Zhongbo Zhou; Le Han (Water Research, 2026)

CYP genetic polymorphism, and CYP3A inducers and inhibitors regulate apatinib metabolism: Consequences for drug exposure and toxicity risks - Zhe Wang; Le-hao Jin; Ni-hong Pang; Jun-er Xu; Xiao-yu Xu; Wei Sun; Xiao-dan Zhang; Jian-chang Qian (Toxicology and Applied Pharmacology, 2026)

A structurally distinct arabinose-bridged arabinogalactan from Lycium barbarum as a TLR4-activating adjuvant for nanovaccine-based cancer immunotherapy - Chun-Jie Bao; Meng-Qiu Liu; Ya-Nan Liu; Li-Qiang Zhao; Yu-Xuan Li; Xin-Lan Zhang; Fang Zhang; Sheng Guo; Er-Xin Shang; Jia-Lun Duan; Jin-Ao Duan (Carbohydrate Polymers, 2026)

The effect of sulfamethoxazole on methanogenesis and intracellular and extracellular antibiotic resistant genes transmission in anaerobic granular sludge - Li-qiang Yu; Ying Chen; Dong-er Wang; Bing Yao; Fan Yuan; Yu-chen Yan; Lan-bin Zhang; Jing-ying Liu; Min Liu (Environmental Research, 2025)

Evaluation of CIRBP and ONECUT2 for fatal hypothermia identification — a pilot study - Gang Chen; Xiangmeng Wang; Jiaxin Qi; Yue Sun; Zhe Wu; Junmiao Xu; Haoze Huang; Qiaoyi Xu; Yu Zhang; Er Xu; Chongjian Xia; Xin Huang; et al. (Cryobiology, 2025)

Influence of prolonged exposure to acetamiprid on the toxicology of the decapod crustacean Pacific white shrimp Penaeus vannamei - Zhen-Fei Li; Zhi Luo; Zhi-Yu Lin; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Physiological, biochemical, and transcriptomic analyses unveil the mechanisms of melatonin in improving wheat stripe rust resistance - Da-Yan Zhang; Jia-Bao Yue; Nan Wu; Yang Wu; Huai-Yu Zhang; Shu Yuan; Ming Yuan; Shozeb Haider; Yang-Er Chen (Plant Science, 2025)

C4-HSL-mediated quorum sensing: Future-oriented technology to promote nitrification process of SBBR mud-film composite system at ultra-low temperatures - Yu-Chen Yan; Ying Chen; Dong-er Wang; Cheng-Yu Yang; Tao Ma; Ye Du; Min Liu (Chemical Engineering Journal, 2025)

A holistic seismic performance evaluation of irregular curved bridges with precast segmental piers considering SSI and depth-varying spatial motion inputs - Yu-Cheng Diao; Chao Li; Hong-Nan Li; Hui-Hui Dong; Er-Tong Hao (Soil Dynamics and Earthquake Engineering, 2025)

Metagenomics and targeted metabolite analysis elucidating the xenobiotics biodegradation and metabolism pathways during sludge aerobic composting - Siying Cai; Xinyu Zhang; Aoxiang Huang; Xuejun Xiong; Er Li; Yu Zhang; Hang Su; Hongxiang Chai; Jianbo Zhang; Dongsheng Wang; Chengzhi Hu; Weijun Zhang (Chemical Engineering Journal, 2025)

Integration of Multi-omics Data Based on Deep Learning for Subtyping of Low-Grade Glioma - Huilin Li; Musu Li; Yue Sun; Er Yu; Jiahe Pan; Yiwen Wu; Zixuan Lu; Hongmei Wo; Fang Shao; Dongfang You; Shaowen Tang; Yang Zhao; et al. (Journal of Molecular Neuroscience, 2025)

Ecological risks under combined pollution: Toxicological effects of clothianidin and microplastics on Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Aquatic Toxicology, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Experimental investigation on sedimentation characteristics of coastal slurry by flocculation - Yu-Xuan Wang; Zhi-Feng Wang; Hong-Tao Chang; Er-Bo Wang (Marine Georesources & Geotechnology, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

An enhanced understanding of the lateral response of large-diameter monopile: Development of a new P -y curve - Qian Xia; Chao Hu; Er Xian Zeng; Hong Yu Tang; Jun Jie Dong; Fei Xu; Jiang Tao Yi (Marine Georesources & Geotechnology, 2025)

Mechanism of mechanical force direction and intensity during sheeting on the rheological behavior of dough and gluten protein structure - Yu-ling Yang; Long Yang; Er-qi Guan; Ke Bian (Food Chemistry, 2025)

Ginkgoites manchurica from the Lower Cretaceous Shahezi Formation of Liaoning, China, and its palaeoclimate implications - Yan Liu; Qiao-Er Ying; Qi-Jia Li; Ning Zhou; Chao Zhang; Yu-Jin Zhang; Xiao Tan; Fei Liang (Palaeoworld, 2025)

Fossil wood of Pinus from the Pliocene of western Yunnan, China and its palaeoclimatic implications - Zhi-Hui Song; Zhuo-Er Wang; Rui Cao; Zhao-Shuai Wang; Huai Wang; Gui-Hua Chen; Jing-Yu Wu (Review of Palaeobotany and Palynology, 2025)

Innovative far-infrared radiation assisted pulsed vacuum freeze-drying of banana slices: Drying behaviors, physicochemical properties and microstructural evolution - Ming-Qiang Xu; Bu-Er Ha; Sriram K. Vidyarthi; Feng-Lun Zhang; Fan Yang; Yu-Hao Jiang; An-An Zhang; Weiqiao Lv; Hong-Wei Xiao (Innovative Food Science & Emerging Technologies, 2025)

A multifaceted assessment and response framework for land use-based carbon metabolism: From Intra-City to Inter-City dynamics - Shiyi Wang; Yan Li; Xinhui Feng; Er Yu; Jiayu Yang (Environmental Impact Assessment Review, 2025)

Corrigendum to “Cryopreservation of porcine skin-derived stem cells using melatonin or trehalose maintains their ability to self-renew and differentiate” [Cryobiology 107 (2022) 23–34] - Jia-Dong Sun; Yu Sun; Tian Qiao; Shu-Er Zhang; Paul W. Dyce; Yuan-Wei Geng; Ping Wang; Wei Ge; Wei Shen; Shun-Feng Cheng (Cryobiology, 2025)

Combined exposure effects: Multilevel impact analysis of cycloxaprid and microplastics on Penaeus vannamei - Zhi-Yu Lin; Zhi Luo; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Physalis floridana suppresses the expression of trehalase gene HvTREs in Henosepilachna vigintioctopunctata (Coleoptera: Coccinellidae) for defense against herbivorous insects - Xian-Zhong Wang; Si-Jing Wan; Bin-Er He; Shuang-Le Wang; Tian-Wen Wang; Liu-He Yu; Shi-Gui Wang; Hui-Zhong Wang; Bin Tang; Jiang-Jie Lu (Journal of Pest Science, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Late Neogene monsoonal climate in the southeastern margin of the Tibetan Plateau revealed by leaf physiognomy evidence - Zhuo-Er Wang; Gui-Hua Chen; Rui Cao; Zhi-Hui Song; Zhao-Shuai Wang; Huai Wang; Su-Ting Ding; Jing-Yu Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Source apportionment and influencing factors of surface water pollution through a combination of multiple receptor models and geodetector - Er Yu; Yan Li; Feng Li; Congying He; Xinhui Feng (Environmental Research, 2024)

SLC10A1 rs2296651 variant (S267F mutation) predicts biochemical traits, hepatitis B virus infection susceptibility and the risk of gallstone disease - Yu-Lin Ko; Wei-Lun Tuan; Ming-Sheng Teng; Wei-Chih Su; Chia‑Chi Wang; Leay-Kiaw Er; Semon Wu; Lung-An Hsu (Molecular Genetics and Genomics, 2024)

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Impact of a Potent Strain of Plant Growth-Promoting Bacteria (PGPB), Bacillus subtilis S1 on Bacterial Community Composition, Enzymatic Activity, and Nitrogen Content in Cucumber Rhizosphere Soils - Meng-Ting Zhang; Yu-Qing Bao; Bao-Yun Feng; Lu-Rong Xu; Ya-Ting Zhang; Er-Xing Wang; Yun-Peng Chen (Current Microbiology, 2024)

Corrigendum to “Aflatoxin B1 disrupts testicular development via the cell cycle-related Ras/PI3K/Akt signaling in mice and pig” [Environ. Pollut. 329 (2023) 121729] - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Zheng-Ning Yuan; Shu-Er Zhang; Ai-Hong Zhao; Huan-Qi Liu; Massimo De Felici; Wei Shen; Xi-Feng Zhang (Environmental Pollution, 2024)

Construction of dual Z-scheme Ag3VO4–BiVO4/InVO4 photocatalysts using vanadium source from spent catalysts for contaminated water treatment and bacterial inactivation - Kuen-Chan Lee; Shih-Chieh Hsu; Jen-Hsien Huang; Kuan-Syun Wang; Wei Kong Pang; Chih-Wei Hu; Yi-Jhen Jiang; Er-Chieh Cho; Huei Chu Weng; Ting-Yu Liu (Chemosphere, 2024)

Spatiotemporal non-stationarity analysis of urban environment using multi-source remote sensing in Chinese metropolitan areas - Kaige Lei; Yan Li; Jiwang Guo; Jiayu Yang; Er Yu; Xinhui Feng; Wu Xiao; Tingting He (Journal of Cleaner Production, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

Late Pliocene Bauhinia s.l. (Cercidoideae, Fabaceae) fossils from Tengchong, Yunnan, southwestern China - Rui Cao; Zhi-hui Song; Zhuo-er Wang; Zhao-shuai Wang; Han-shi Li; Jing-Yu Wu; Su-Ting Ding (Review of Palaeobotany and Palynology, 2024)

Developmental toxicity of the neonicotinoid pesticide clothianidin to the larvae of the crustacean Decapoda, Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Journal of Hazardous Materials, 2024)

Three species of rape responded to cadmium and melatonin alleviating Cd-toxicity in species-specific strategy - Xiao-long Qin; Yu-qing Zhao; De-jun Zhang; Ke-yu Wang; Wen-hui Chen; Zi-Zhong Tang; Yang-er Chen; Shu Yuan; Lin Ye; Ming Yuan (Environmental Pollution, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Next-generation neonicotinoid: The impact of cycloxaprid on the crustacean decapod Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Chemosphere, 2024)

POPs identification using simple low-code machine learning - Lei Xin; Haiying Yu; Sisi Liu; Guang-Guo Ying; Chang-Er Chen (Science of The Total Environment, 2024)

Impact of urban land development on carbon emission performance based on a multidimensional framework - Xinhui Feng; Xinle Lin; Yan Li; Jiayu Yang; Er Yu; Congying He; Kaige Lei; Weiming Gao (Environmental Impact Assessment Review, 2024)

Integrated transcriptome and metabolome analysis revealed that HaMYB1 modulates anthocyanin accumulation to deepen sunflower flower color - Siqi Ma; Hanlin Zhou; Tingting Ren; Er-ru Yu; Bin Feng; Juying Wang; Chengsheng Zhang; Chao Zhou; Yiqiang Li (Plant Cell Reports, 2024)
Key message HanMYB1 was found to play positive roles in the modulation of anthocyanins metabolism based on the integrative analysis of different color cultivars and the related molecular genetic analyses. Abstract As a high value ornamental and edible crop with various colors, sunflowers ( Helianthus annuus L.) provide an ideal system to understand the formation of flower color. Anthocyanins are major pigments in higher plants, which is associated with development of flower colors and ability of oxidation resistance. Here, we performed an integrative analysis of the transcriptome and flavonoid metabolome in five sunflower cultivars with different flower colors. According to differentially expressed genes and differentially accumulated flavonoids, these cultivars could be grouped into yellow and red. The results showed that more anthocyanins were accumulated in the red group flowers, especially the chrysanthemin. Some anthocyanins biosynthesis-related genes like UFGT (UDP-glycose flavonoid glycosyltransferase) also expressed more in the red group flowers. A MYB transcriptional factor, HanMYB1, was found to play vital positive roles in the modulation of anthocyanins metabolism by the integrative analysis. Overexpressed HanMYB1 in tobacco could deepen the flower color, increase the accumulation of anthocyanins and directly active the express of UFGT genes. Our findings indicated that the MYB transcriptional factors provide new insight into the dynamic regulation of the anthocyanin biosynthesis in facilitating sunflower color formation and anthocyanin accumulation.

Leucine improves dietary protein use efficiency by regulating protein synthesis by activating amino acid transporters and the mTORC1 pathways in Chinese mitten crab (Eriocheir sinensis) - Ming-Qi Song; Qiu-Ran Yu; Er-Chao Li; Ying Song; Xin-Yu Cai; Yu-Xiang Huang; Chuan-Jie Qin; Xiao-Dan Wang; Jian-Guang Qin; Li-Qiao Chen (Aquaculture, 2024)

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Real-time and quantitative protein detection via polyacrylamide gel electrophoresis and online intrinsic fluorescence imaging - Zixian Yu; Yiren Cao; Youli Tian; Weicheng Ji; Ke-Er Chen; Zihao Wang; Jicun Ren; Hua Xiao; Lu Zhang; Weiwen Liu; Liuyin Fan; Qiang Zhang; et al. (Analytica Chimica Acta, 2024)

Petrogenesis and tectonic implications of the Silurian adakitic granitoids in the eastern segment of the Qilian Orogenic Belt, Northwest China - Jiao-Long Zhao; Xiao-Jun Huang; Pei-Qing Hu; Zhen-Xi Yang; Ying Fan; Er-Teng Wang; Fu-Bo Yang; Jing-Yu Zhang (Acta Geochimica, 2024)

Development of a new method framework to estimate the nonlinear and interaction relationship between environmental factors and soil heavy metals - Kaige Lei; Yan Li; Yanbin Zhang; Shiyi Wang; Er Yu; Feng Li; Fen Xiao; Fang Xia (Science of The Total Environment, 2023)

Fossil samaras of Acer L. (Sapindaceae) from the Upper Pliocene of western Yunnan, southwestern China - Zhuo-Er Wang; Rui Cao; Hong Ding; Yong-Tong Huang; Zhi-Hui Song; Su-Ting Ding; Jing-Yu Wu (Palaeobiodiversity and Palaeoenvironments, 2023)

Machine learning combined with Geodetector quantifies the synergistic effect of environmental factors on soil heavy metal pollution - Kaige Lei; Yan Li; Yanbin Zhang; Shiyi Wang; Er Yu; Feng Li; Fen Xiao; Zhou Shi; Fang Xia (Environmental Science and Pollution Research, 2023)

Impacts of land use transitions on ecosystem services: A research framework coupled with structure, function, and dynamics - Xinhui Feng; Yan Li; Xize Wang; Jiayu Yang; Er Yu; Shiyi Wang; Nengjun Wu; Fen Xiao (Science of The Total Environment, 2023)

Identification and whole-genome sequencing of a bacterial strain isolated from healthy rice plants antagonistic to Magnaporthe oryzae - Hu Zhou; Xiao-jun Chen; Hai-di Liang; Mo-xiong Liu; Xue Zu; Yao-xiong Lu; Jia Zhou; Shun-ming Yang; Lian-fang Yu; Er-ming Liu; Zuo-hua Ren (Physiological and Molecular Plant Pathology, 2023)

Fabrication of highly efficient hydroxyapatite microtubes for uranium sequestration and immobilization - Chuqin Ma; Yu'er Peng; Minhua Su; Gang Song; Diyun Chen (Journal of Environmental Management, 2023)

MOF-derived spinel NiMn2O4/CoMn2O4 heterojunction and its application in a high-performance photocatalyst and supercapacitor - Kuen-Chan Lee; Yu-Sheng Hsiao; Ming-Yen Sung; Yi-Lun Chen; Nian-Jheng Wu; Jen-Hsien Huang; Er-Chieh Cho; Huei Chu Weng; Shih-Chieh Hsu (Journal of Environmental Chemical Engineering, 2023)

Dental Pulp Stem Cell-Derived Conditioned Medium Alleviates Subarachnoid Hemorrhage-Induced Microcirculation Impairment by Promoting M2 Microglia Polarization and Reducing Astrocyte Swelling - Ling-Yu Yang; Yong-Ren Chen; Jing-Er Lee; Kuo-Wei Chen; Hui-Tzung Luh; Yi-Tzu Chen; Kuo-Chuan Wang; Sung-Tsang Hsieh (Translational Stroke Research, 2023)
Aneurysmal subarachnoid hemorrhage (SAH) can cause severe neurological deficits and high mortality. Early brain edema following SAH contributes to the initiation of microcirculation impairment and may further lead to delayed ischemic neurologic deficit (DIND). This study aimed to investigate whether dental pulp stem cell conditioned medium (DPSC-CM) ameliorates SAH-induced microcirculation impairment and the underlying mechanisms. SAH was induced via intrathecal injection of fresh autologous blood in Wistar male adult rat. DPSC-CM or DPSC-CM + insulin growth factor-1 (IGF-1) antibody was randomly administered by intrathecal route 5 min after SAH induction. To evaluate the underlying mechanisms of DPSC-CM in the treatment of SAH, primary rat astrocyte and microglia co-cultures were challenged with hemolysate or SAH-patient CSF in the presence or absence of DPSC-CM. The results showed that in vivo, DPSC-CM treatment decreased the brain water content, improved microcirculation impairment and enhanced functional recovery at 24 h post-SAH. DPSC-CM treatment also alleviated the expressions of water channel protein aquaporin-4 (AQP4) and pro-inflammatory cytokines, and enhanced the expressions of anti-inflammatory factors in the cortical region. However, all the beneficial effects of DPSC-CM were abrogated after treatment with IGF-1 neutralizing antibody. The in vitro results further showed that DPSC-CM treatment reduced hemolysate/SAH-patient CSF-induced astrocyte swelling and promoted M2 microglia polarization, partially through IGF-1/AKT signaling. The data suggested that DPSC-CM significantly reduced brain edema and rescued microcirculation impairment with concomitant anti-inflammatory benefits after SAH, and may potentially be developed into a novel therapeutic strategy for SAH.

Aflatoxin B1 affects porcine alveolar macrophage growth through the calcium signaling pathway mediated by the ceRNA regulatory network - Yu Tian; Pei-Yu Dong; Sheng-Lin Liang; Long Li; Shu-Er Zhang; Francesca Gioia Klinger; Wei Shen; You-Yu Yan; Xi-Feng Zhang (Molecular Biology Reports, 2023)

Exposure to incense burning, biomarkers, and the physical health of temple workers in Taiwan - Su-Er Guo; Pamela A. Ratner; Sung-Chih Tseng; Chieh-Mo Lin; Miao-Ching Chi; Chiang-Wen Lee; Ying-Chun Yu (Environmental Science and Pollution Research, 2023)
Incense burning releases heavy particulate matter (PM) and nitrogen dioxide (NO 2 ), known to have adverse effects on human health. Long-term exposure to PM and NO 2 increases inflammatory cytokine levels and can induce respiratory diseases. This study examined the association between incense burning exposure and the health status, especially inflammatory biomarkers, of temple workers and volunteers in Taiwan. The longitudinal observational study compared adult temple workers and volunteers, with long-term incense burning exposure, to residents from outpatient clinics in the Chiayi area. Forced expiratory volume in 1 s (FEV1) and serum and exhaled breath condensate (EBC) cytokines were assessed. Nonparametric Mann-Whitney U tests were used to compare cytokine levels of the exposure and control groups during the cold and hot weather seasons. FEV1 was significantly more diminished in the exposed group than in the control group during the cold season. Exposure status was associated with greater hot-cold seasonal differences in serum interleukins (IL)-1β (regression coefficient ( B ) = 6.6, 95% confidence interval (CI) = 5.0 to 8.3, p < .001), IL17-A ( B = 2.4, 95% CI = 0.3 to 4.5, p = .03), and plasminogen activator inhibitor [PAI]-1 ( B = 5.4, 95% CI = 1.5 to 9.3, p = .009). After adjusting for confounders, the groups’ serum levels of IL-1β, IL-17A, and PAI-1 significantly differed. EBC cytokines did not show significant differences. Elevated levels of IL-1β, IL17-A, and PAI-1 have been associated with various autoinflammatory syndromes and diseases. Given the cultural significance of incense burning, culturally sensitive interventions, including education, policy development, and program implementation, are crucial to protect individuals’ health, especially temple workers, from the adverse effects of exposure, addressing the manufacture, importation, and sale of incense.

Detection of global change with meiofauna and its benthic environment in a shelf sea cold water mass ecosystem - Hong Zhou; Karim MD Abdul; Qing Yu; Xiaoshou Liu; Er Hua; Yang Lou; Saif MD Uddin; Rebeca Montero-Taboada; Zhinan Zhang (Regional Studies in Marine Science, 2023)

Molybdenum-Induced Apoptosis of Splenocytes and Thymocytes and Changes of Peripheral Blood in Sheep - Shu-gang Cui; Yu-ling Zhang; Hong-wei Guo; Bian-hua Zhou; Er-jie Tian; Jing Zhao; Lin Lin; Hong‑wei Wang (Biological Trace Element Research, 2023)

Spatialization and driving factors of carbon budget at county level in the Yangtze River Delta of China - Shiyi Wang; Yan Li; Feng Li; Daofu Zheng; Jiayu Yang; Er Yu (Environmental Science and Pollution Research, 2023)

A peptide scanned from the capsid protein of NNV induces effective immune response and protects pearl gentian groupers from viral nervous necrosis - Gao-Yang Liu; Zhong-Yu Zhang; Fei Ling; Peng-Fei Li; Er-Long Wang; Gao-Xue Wang (Aquaculture, 2023)

Insights into the release of triclosan from microplastics in aquatic environment assessed with diffusive gradient in thin-films - Si-Si Liu; Yu-Wei Jia; Xiao-Yuan Guo; Jian-Liang Zhao; Yue Gao; Andy J. Sweetman; Guang-Guo Ying; Li Xu; Chen Tu; Chang-Er Chen (Science of The Total Environment, 2023)

Use and non-use of parks are dictated by nature orientation, perceived accessibility and social norm which manifest in a continuum - Angelia SIA; Puay Yok TAN; Yu Jin KIM; Kenneth Boon Hwee ER (Landscape and Urban Planning, 2023)

Aflatoxin B1 disrupts testicular development via the cell cycle-related Ras/PI3K/Akt signaling in mice and pig - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Zheng-Ning Yuan; Shu-Er Zhang; Ai-Hong Zhao; Huan-Qi Liu; Massimo De Felici; Wei Shen; Xi-Feng Zhang (Environmental Pollution, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

Oxidative stress mediates the associations between phthalate exposures and thyroid cancer/benign nodule risk - Chong Liu; Long-Qiang Wang; Min Zhang; Yan-Ling Deng; Qiong Luo; Er-Nan Liu; Pan-Pan Chen; Yu Miao; Pan Yang; Qiang Zeng (Environmental Pollution, 2023)

Casing deformation risk assessment method based on fault–slip theory and its application to shale formations - Jun-Chuan Gui; Yu Sang; Bo Zeng; Hao-Yong Huang; Qi-Yong Gou; Jun-Feng Li; Er-Si Xu; Guang-Hai Zhong (Applied Geophysics, 2023)

Study on characteristic and mechanism involved in the formation of N-nitrosodimethylamine precursors during microbial metabolism of amino acids - Er Bei; Zhiwei Ye; Xiuli Chen; Xiao Li; Jun Wang; Yu Qiu; Shuguang Xie; Chao Chen (Science of The Total Environment, 2023)

Occurrence, fate and ecological risks of 90 typical emerging contaminants in full-scale textile wastewater treatment plants from a large industrial park in Guangxi, Southwest China - Si-Si Liu; Wen-Dan You; Chang-Er Chen; Xin-Yu Wang; Bin Yang; Guang-Guo Ying (Journal of Hazardous Materials, 2023)

Renewable pickering emulsion system based on bifunctional materials for highly efficient fuel oil desulfurization without stirring - Shuai-Yong Dou; Jia-Yu An; Yan-Ru Feng; Kang Liu; Xuan Wang; Bo-Wen Zhang; Jing-Xuan Zhang; Er-Hong Duan; Ai-Bin Kang (Fuel, 2023)

Caspar negatively regulates anti-bacterial immunity by controlling the nuclear translocation of Relish in Chinese mitten crab (Eriocheir sinensis) - Zhi Luo; Yu-Kai Qin; Ke Zhao; Xing-Yu Nan; Wei-Wei Li; Er-Chao Li; Qun Wang (Fish & Shellfish Immunology, 2023)

Reactive Green 19 dye-ligand immobilized on the aminated nanofiber membranes for efficient adsorption of lysozyme: Process development and optimization in batch and flow systems - Jia-Ling Hsu; Steven S.-S. Wang; Chien Wei Ooi; Xue Er Crystal Thew; You-Ren Lai; Chen-Yaw Chiu; Michael Hsu; Kuei-Hsiang Chen; Yu-Kaung Chang (Food Chemistry, 2023)

Behavior of wheat flour dough at different pretreated temperatures through rheological characteristics and molecular interactions of proteins - Yu-ling Yang; Er-qi Guan; Ting-jing Zhang; Fei Xu; Meng-meng Li; Ke Bian (Food Chemistry, 2023)

Insect biorefinery: A circular economy concept for biowaste conversion to value-added products - Phei Er Kee; Yu-Shen Cheng; Jo-Shu Chang; Hip Seng Yim; John Choon Yee Tan; Su Shiung Lam; John Chi-Wei Lan; Hui Suan Ng; Kuan Shiong Khoo (Environmental Research, 2023)

Maternal exposure to nitrosamines in drinking water during pregnancy and birth outcomes in a Chinese cohort - Qiong Luo; Yu Miao; Chong Liu; Er Bei; Jin-Feng Zhang; Ling-Hua Zhang; Yan-Ling Deng; Yu Qiu; Wen-Qing Lu; J. Michael Wright; Chao Chen; Qiang Zeng (Chemosphere, 2023)

Melatonin improves the removal and the reduction of Cr(VI) and alleviates the chromium toxicity by antioxidative machinery in Rhodobacter sphaeroides - Hao-Tian Mao; Lun-Xing Chen; Meng-Ying Zhang; Qiu-Yun Shi; Hong Xu; Da-Yan Zhang; Zhong-Wei Zhang; Ming Yuan; Shu Yuan; Huai-Yu Zhang; Yan-Qiu Su; Yang-Er Chen (Environmental Pollution, 2023)

Temperature-dependent effects of neonicotinoids on the embryonic development of zebrafish (Danio rerio) - Yolina Yu Lin Wang; Yan-Er Cai; Syed Shabi Ul Hassan Kazmi; Jing Yang; Yuwen Wang; Ping Li; Wenhua Liu; Zhen Wang (Frontiers in Marine Science, 2023)
The agricultural use of neonicotinoids is increasing worldwide and poses a threat to non-target organisms. The existing toxicity data of neonicotinoids that is mainly focused on widely used neonicotinoids ignores the influence of environmental factors, like temperature, related to climate changes, etc . To fill this data gap, the present study assessed the temperature-dependent toxicity of six neonicotinoids at four temperatures. Briefly, a fish embryo toxicity test was performed at the following temperatures—20, 23, 28, and 33°C—on zebrafish embryos to evaluate the lethal and sublethal effects of these toxicants. At 28°C, the lethal toxicity (LC 50 ) values for these toxicants were cycloxaprid—3.36 mg/L, nitenpyram—7.08 mg/L, paichongding—17.2 mg/L, imidaclothiz—738.6 mg/L, dinotefuran—2,096 mg/L, and thiamethoxam—4,293 mg/L, respectively. Among the sublethal effects, the enzymatic activities changed significantly in neonicotinoid treatments, which revealed oxidative stress, metabolic disorders, and neurotoxicity. Particularly, acetylcholinesterase inhibition and glutathione S-transferase activation showed a significant dose–response relationship. However, cycloxaprid, nitenpyram, and paichongding were found to be more potent compared with imidaclothiz and thiamethoxam. The influence of temperature on these neonicotinoids demonstrated an inverted V-shaped relationship, in which toxicity decreased with the increase of temperature and then increased with the increase of temperature after exceeding the optimum temperature. This study provides a reference for the multiscale effects and potential mechanisms of neonicotinoids. Temperature-dependent toxicity is of great significance for future toxicity testing and risk assessment of chemicals in the face of global climate changes.

The effect of nitrite and nitrate treatment on growth performance, nutritional composition and flavor-associated metabolites of grass carp (Ctenopharyngodon idella) - Jun-Ming Zhang; Bing Fu; Yi-chao Li; Jin-Hui Sun; Jun Xie; Guang-Jun Wang; Jing-Jing Tian; Gen Kaneko; Er-Meng Yu (Aquaculture, 2023)

Sex-related differences in safety profiles, pharmacokinetics and tissue distribution of sinomenine hydrochloride in rats - Hong Huang; Er-Bing Zhang; Ou-Yang Yi; Han Wu; Guiming Deng; Yu-Ming Huang; Wen-Liang Liu; Jian-Ye Yan; Xiong Cai (Archives of Toxicology, 2022)

Ancient DNA from Tubo Kingdom-related tombs in northeastern Tibetan Plateau revealed their genetic affinity to both Tibeto-Burman and Altaic populations - Xue-Er Yu; Chang Sun; Ye-Tao Zou; Ji-Yuan Li; Xiaoyan Ren; Hui Li (Molecular Genetics and Genomics, 2022)

Establishment and application of an anisotropic shale rock physical model in the observation coordinate system - Jun-Chuan Gui; Yu Sang; Jian-Chun Guo; Bo Zeng; Yi Song; Hao-Yong Huang; Er-si Xu; Ya-xi Chen (Applied Geophysics, 2022)

YAP regulates porcine skin-derived stem cells self-renewal partly by repressing Wnt/β-catenin signaling pathway - Hong-Chen Yan; Yu Sun; Ming-Yu Zhang; Shu-Er Zhang; Jia-Dong Sun; Paul W. Dyce; Francesca Gioia Klinger; Massimo De Felici; Wei Shen; Shun-Feng Cheng (Histochemistry and Cell Biology, 2022)

Dehydroabietic acid improves nonalcoholic fatty liver disease through activating the Keap1/Nrf2-ARE signaling pathway to reduce ferroptosis - Gai Gao; Zhishen Xie; Er-wen Li; Yong Yuan; Yu Fu; Pan Wang; Xiaowei Zhang; Yonghui Qiao; Jiangyan Xu; Christian Hölscher; Hui Wang; Zhenqiang Zhang (Journal of Natural Medicines, 2021)

Chemical constituents from Jasminum pentaneurum Hand.-Mazz and their cytotoxicity against human cancer cell lines - Wei Wei; Er-Wei Hao; Meng Zhang; Xiang-Long Pan; Jian-Feng Qin; Jin-Ling Xie; Jiang-Yu Zhou; Xiao-Tao Hou; Jia-Gang Deng (Natural Product Research, 2021)

Study on the small strain shear modulus of saturated sand-fines mixtures by bender element test - Bin Ruan; Yu Miao; Ke Cheng; Er-lei Yao (European Journal of Environmental and Civil Engineering, 2021)

Environmental Influence on the Spatiotemporal Variability of Fishing Grounds in the Beibu Gulf, South China Sea - Yanfeng Wang; Lijun Yao; Pimao Chen; Jing Yu; Qia’er Wu (Journal of Marine Science and Engineering, 2020)
The spatiotemporal distribution of fishing grounds in the Beibu Gulf and its relationship with marine environment were analyzed using the survey data of light falling-net vessels and satellite remote sensing data including sea surface temperature (SST), chlorophyll a concentration (Chl a) and net primary production (NPP), based on the generalized additive model (GAM) and the center of gravity (COG) of fishing grounds. The results showed that the total deviance explained by GAM for the catch per unit effort (CPUE) in the Beibu Gulf was 42.9%, in which SST was the most important influencing factor on CPUE, with a relative contribution of 40%; followed by latitude, Chl a, month and NPP, with relative contributions of 25.2%, 19%, 10.4% and 5.4%, respectively. Fishing grounds in the Beibu Gulf were mainly distributed in waters with SST of 27–29 °C, Chl a of 0.5–1.5 mg m−3 and NPP of 500–700 mg m−2 d−1. Light falling-net fishing grounds were concentrated in waters with latitude of 18.5° N and 20–20.25° N. There was a significant correlation between the mean latitude of optimum NPP and the latitudinal COG of CPUE, with the R2 being 0.91. These were connected with environmental factors such as the northeast monsoon that began in autumn and winter, warm pools near 19° N and local upwelling in the Beibu Gulf.

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Regulation of bile acid metabolism-related signaling pathways by gut microbiota in diseases - Er-teng Jia; Zhi-yu Liu; Min Pan; Jia-feng Lu; Qin-yu Ge (Journal of Zhejiang University-SCIENCE B, 2019)

Polymorphisms in the APOBEC3G gene of Chinese rhesus macaques affect resistance to ubiquitination and degradation mediated by HIV-2 Vif - Zhi-Qiang Jiang; Xu-Rong Yao; Hang Yu; Yue-Er Lu; Bei-Lei Liu; Feng-Liang Liu; Ya-Bin Jin; Min Zhuo; Yong-Tang Zheng; Fei Ling (Archives of Virology, 2019)

The anxiolytic effects of Bai Le Mian capsule, a traditional Chinese hypnotic in mice - Tian-Xiao Wang; Yu-Er Wu; Wei Xu; Wan-Kun Gong; Jian Ni; Wei-Min Qu; Zhi-Li Huang (Sleep and Biological Rhythms, 2019)

Lipid accumulation in grass carp (Ctenopharyngodon idellus) fed faba beans (Vicia faba L.) - Jing-jing Tian; Hong Ji; Yi-fei Wang; Jun Xie; Guang-jun Wang; Zhi-fei Li; Er-meng Yu; De-guang Yu; Kai Zhang; Wang-bao Gong (Fish Physiology and Biochemistry, 2019)

Comparison of Photosynthetic Characteristics and Antioxidant Systems in Different Wheat Strains - Yang-Er Chen; Yan-Qiu Su; Chao-Ming Zhang; Jie Ma; Hao-Tian Mao; Zi-Han Yang; Ming Yuan; Zhong-Wei Zhang; Shu Yuan; Huai-Yu Zhang (Journal of Plant Growth Regulation, 2018)

High-depth whole genome sequencing of an Ashkenazi Jewish reference panel: enhancing sensitivity, accuracy, and imputation - Todd Lencz; Jin Yu; Cameron Palmer; Shai Carmi; Danny Ben-Avraham; Nir Barzilai; Susan Bressman; Ariel Darvasi; Judy H. Cho; Lorraine N. Clark; Zeynep H. Gümüş; Vijai Joseph; et al. (Human Genetics, 2018)

Seasonal variation and source apportionment of PM2.5-bound trace elements at a coastal area in southwestern Taiwan - Su-Lun Hwang; Miao-Ching Chi; Su-Er Guo; Yu-Ching Lin; Chiang-Ting Chou; Chieh-Mo Lin (Environmental Science and Pollution Research, 2018)

Arabidopsis heat stress transcription factors A2 (HSFA2) and A3 (HSFA3) function in the same heat regulation pathway - Xiao-dong Li; Xiao-li Wang; Yi-Ming Cai; Jia-hai Wu; Ben-tian Mo; Er-ru Yu (Acta Physiologiae Plantarum, 2017)

Effects of nitrogen and phosphorus enrichment on growth and photosynthetic assimilation of carbon in a green tide-forming species (Ulva prolifera) in the Yellow Sea - Shaoxiang Li; Kefeng Yu; Yuanzi Huo; Jianheng Zhang; Hailong Wu; Chun’er Cai; Yuanyuan Liu; Dingji Shi; Peimin He (Hydrobiologia, 2016)

Targeted next-generation sequencing for molecular diagnosis of endometriosis-associated ovarian cancer - Tze-Kiong Er; Yu-Fa Su; Chun-Chieh Wu; Chih-Chieh Chen; Jing Wang; Tsung-Hua Hsieh; Marta Herreros-Villanueva; Wan-Tzu Chen; Yi-Ting Chen; Ta-Chih Liu; Hung-Sheng Chen; Eing-Mei Tsai (Journal of Molecular Medicine, 2016)

Agriculture driving male expansion in Neolithic Time - Chuan-Chao Wang; Yunzhi Huang; Xue’er Yu; Chun Chen; Li Jin; Hui Li (Science China Life Sciences, 2016)

Ameliorative effects of Qingfei Tongluo formula on experimental mycoplasmal pneumonia in mice - Yong-hong Jiang; Jian-er Yu; Ai-hua Guo; Xiao Li; Yan Lin; Zhi-yan Jiang; Zhen Xiao (Journal of Natural Medicines, 2016)

A combination of chitosan and chemical fertilizers improves growth and disease resistance in Begonia × hiemalis Fotsch - Yang-Er Chen; Shu Yuan; Han-Mei Liu; Zhi-Yu Chen; Ying-Hong Zhang; Huai-Yu Zhang (Horticulture, Environment, and Biotechnology, 2016)

Ethyl methane sulfonate induces disease resistance in Begonia × hiemalis Fotsch. - Yang-Er Chen; Ying-Hong Zhang; Shu Yuan; Han-Mei Liu; Xian-Yin Zeng; Huai-Yu Zhang (Horticulture, Environment, and Biotechnology, 2014)

Differential expression patterns and a novel interaction factor of Damaged DNA Binding Protein 1A (DDB1A) and DDB1B in Arabidopsis thaliana - Pei Hou; Peng-fei Ren; De-er Zeng; Gui-rong Yu; Wei Tang; Xu Zheng; Jian-ping Yang; Yongsheng Liu (Journal of Plant Biology, 2014)

Bex2 Controls Proliferation of Human Glioblastoma Cells Through NF-κB Signaling Pathway - Qingming Meng; Tongle Zhi; Yuewen Chao; Er Nie; Xuebin Xu; Qiong Shi; Lei Hua; Lei Wang; Wenjian Zhan; Yong Wang; Xiuping Zhou; Rutong Yu (Journal of Molecular Neuroscience, 2014)

Pattern of benthic biomass size spectra from shallow waters in the East China Seas - Er Hua; Zhinan Zhang; Richard M. Warwick; Ke Deng; Kuixuan Lin; Ruizhao Wang; Zishan Yu (Marine Biology, 2013)

Enhanced biotransformation of 1,3-dichloro-2-propanol to epichlorohydrin via resin-based in situ product removal process - Shu-Ping Zou; Er-Hong Du; Zhong-Ce Hu; Yu-Guo Zheng (Biotechnology Letters, 2013)

Partial or complete substitution of fish meal with soybean meal and cottonseed meal in Chinese mitten crab Eriocheir sinensis diets - Hai-Bo Jiang; Li-Qiao Chen; Jian-Guang Qin; Lu-Jiao Gao; Er-Chao Li; Na Yu; Sheng-Ming Sun; Xue-Qin Jiang (Aquaculture International, 2013)

A New Elasto-Viscoplastic Damage Model Combined with the Generalized Hoek–Brown Failure Criterion for Bedded Rock Salt and its Application - Lin-jian Ma; Xin-yu Liu; Qin Fang; Hong-fa Xu; Hui-min Xia; Er-bing Li; Shi-gang Yang; Wen-pei Li (Rock Mechanics and Rock Engineering, 2013)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

Strontium Ranelate Prevents Bone Loss in a Rat Model of Localized Muscle Paralysis - Zhi-Feng Sheng; Yu-Lin Ma; Dejun Tong; De-Yu Fang; Qing-Chun Liang; Li-Hong Liu; Jian Zhang; Er-Yuan Liao (Annals of Biomedical Engineering, 2012)

A Novel Mutation in CACNA1S Gene Associated with Hypokalemic Periodic Paralysis Which has a Gender Difference in the Penetrance - Fei-Feng Li; Qian-Qian Li; Zhen-Xuan Tan; Si-Yao Zhang; Ji Liu; Er-ying Zhao; Gui-Chun Yu; Jin Zhou; Li-Ming Zhang; Shu-Lin Liu (Journal of Molecular Neuroscience, 2012)

Interleukin-8-251A/T polymorphism and Helicobacter pylori infection influence risk for the development of gastric cardiac adenocarcinoma in a high-incidence area of China - Liwei Zhang; Chaoqun Du; Xiaoqing Guo; Li Yuan; Weiwei Niu; Weifang Yu; Limian Er; Shijie Wang (Molecular Biology Reports, 2010)

Assessing the combination effects of environmental estrogens in fish - Hui Zhang; Fan-Xiang Kong; Yang Yu; Xiao-Li Shi; Min Zhang; Hong-Er Tian (Ecotoxicology, 2010)

Estimates of autumntime benthic secondary production in Laizhou Bay and adjacent Bohai Sea waters - Er Hua; Hong Zhou; Zhinan Zhang; Zishan Yu (Journal of Ocean University of China, 2010)

Isolation of Tanichthys albonubes β actin gene and production of transgenic Tanichthys albonubes - Yu Er-meng; Ye Xing; Wang Hai-ying; Bai Jun-jie; Xia Shi-ling; Lao Hai-hua; Jian Qing (Fish Physiology and Biochemistry, 2010)

Somatic embryogenesis and plant regeneration in two wild cotton species belong to G genome - Shu-Feng Yan; Qiao Zhang; Jing-Er Wang; Yu-Qiang Sun; M. K. Daud; Shui-Jin Zhu (In Vitro Cellular & Developmental Biology - Plant, 2010)

Generation of disinfection by-products (DBPs) at two advanced water treatment plants - Jie-Chung Lou; Chien-Er Huang; Jia-Yun Han; Yu-Jen Huang (Environmental Monitoring and Assessment, 2010)

Association of the DNMT3B polymorphism with colorectal adenomatous polyps and adenocarcinoma - Xiaoqing Guo; Liwei Zhang; Mingli Wu; Na Wang; Yanfeng Liu; Limian Er; Shunping Wang; Yang Gao; Weifang Yu; Hui Xue; Zhibin Xu; Shijie Wang (Molecular Biology Reports, 2010)

The Influence of Center of Rotation on the Assessment of Trabecular Bone Densitometric and Structural Properties - Zhi-Feng Sheng; Ru-Chun Dai; Xian-Ping Wu; Yu-Lin Ma; Kang Xu; Yu-Hai Zhang; Ye-Bin Jiang; Er-Yuan Liao (Annals of Biomedical Engineering, 2008)

Cellular and molecular responses in progressive pseudorheumatoid dysplasia articular cartilage associated with compound heterozygous WISP3 gene mutation - Hou-De Zhou; Yan-Hong Bu; Yi-Qun Peng; Hui Xie; Min Wang; Lin-Qing Yuan; Yi Jiang; Duo Li; Qi-You Wei; Yu-Ling He; Tao Xiao; Jiang-Dong Ni; et al. (Journal of Molecular Medicine, 2007)

Ciona intestinalis as an emerging model organism: Its regeneration under controlled conditions and methodology for egg dechorionation - Li-ping Liu; Jian-hai Xiang; Bo Dong; Pavanasam Natarajan; Kui-jie Yu; Nan-er Cai (Journal of Zhejiang University-SCIENCE B, 2006)